Axitinib overcomes multiple imatinib resistant cKIT mutations including the gatekeeper mutation T670I in gastrointestinal stromal tumors. (May 2019) - Liu, Feiyang; Zou, Fengming; Chen, Cheng; Yu, Kailin; Liu, Xiaochuan; Qi, Shuang; Wu, Jiaxin; Hu, Chen; Hu, Zhenquan; Liu, Juan; Liu, Xuesong; Wang, Li; et al.
Background: cKIT kinase overexpression and gain-of-function mutations are the critical pathogenesis of gastrointestinal stromal tumors (GISTs). Although the multiple kinase inhibitors such as imatinib, sunitinib, and regorafenib have been approved for GISTs, the acquisition of polyclonal secondary resistance mutations in KIT is still a limitation for GIST treatment. Here we explored the KIT inhibitory activity of axitinib in preclinical models and describe initial characterization of its activity in GIST patient-derived primary cells. Methods: The activities of axitinib against mutant KIT were evaluated using protein-based assay and a panel of engineered and GIST-derived cell lines. The binding modes of axitinib-KIT/KIT mutants were analyzed. Four primary cells derived from GIST patients were also used to assess the drug response of axitinib. Results: Axitinib exhibited potent activities against a variety of cKIT associated primary and secondary mutations. It displayed better activity against cKIT wild-type, cKIT V559D/A/G, and L576P primary gain-of-function mutations than imatinib, sunitinib, and regorafenib. In addition, it could inhibit imatinib resistant cKIT T670I and V654A mutants in vitro and in vivo GIST preclinical models. Conclusion: Our results provide the basis for extending the application of axitinib to GISTs patients who are unresponsive or intolerant to the current therapies.